(untitled) (Scientific journal of the Fergana State University, 2025)
Mythonyms, enriched with mythological, linguistic, and cultural significance, play a central role in J.R.R. Tolkien’s works and his world. This article examines the origins, meanings, and functions of mythonyms in Tolkien’s stories, as well as their contribution to world-building, character depiction, racial groups, and mythological landscapes. Using mixed methods, the study analyzes around 50 mythonyms mentioned in The Silmarillion, The Hobbit, and The Lord of the Rings. The results reveal that Tolkien’s mythonyms harmonize the influences of Germanic, Old English, and Finnish mythologies, highlighting their role in evoking cultural memory and increasing reader engagement. Artistic imagery and semantic fields underscore the significance of mythonyms in enriching the mythopoetic structure. This study presents a linguopoetic description of myth.